Sistema de monitoramento da qualidade do ar utilizando uma rede LPWAN - Chabi, Abdel Fadyl (Brasil, 2022)
In this research work, a hardware and software system that uses low-cost wireless sensors to monitor some pollutants in the air and variables such as temperature, air humidity and geographic coordinates in order to monitor air quality from a particular location was developed. LoRa technology with an average range of 5km in urban areas and 10km in rural areas was used to perform this monitoring. The developed system has a web Internet of Things (IoT) platform in which a dashboard that receives the variables being monitored in real time and displays them in an intuitive way for the user is configured. Tests were performed in different parts of the city to validate the measurements of the developed system. The measurements obtained were compared to the standards of the world health organization to assess the possible health risks of air pollution in the chosen locations. The viability of the developed system proves the possibility of having mobile air quality monitoring stations, with low cost for large-scale monitoring in the future.